Inorganic transparent intumescent interlayer coatings for fire rated glass - Lin, Nicole Xi (Nanyang Technological University, 2023)
An inorganic alkali silicate based fire-resistant coating has been developed for laminated glass to slow the spread of heat in the case of a fire breakout by the mechanism of intumescing. Various formulations of the interlayer coating were synthesized with different SiO2 : M2O molar ratios using colloidal silica solution with the addition of an alkali silicate. The incorporation of silica particles was found to improve the water stability of hygroscopic silicate-based coatings that are commonly used commercially.